EFEKTIVITAS PERMAINAN HOUSE MITIGATION UNTUK MENINGKATKAN SELF-AWARENESS SIAGA BENCANA GEMPA BUMI PADA ANAK USIA 4-5 TAHUN DI PAUD KB GENIUS KIDS KOTA BUKITTINGGI - Sari Kunanti; Enda Puspitasari; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Based on field observations of self-awareness on earthquake disaster preparedness, children aged 4-5 years at PAUD KB Genius Kids, Bukittinggi City, still need to be stimulated and educated to increase self-awareness on earthquake disaster preparedness. it might happen to them. In disaster preparedness education, what researchers do has an implementation flow that will be integrated into the learning process. Seeing the phenomenon above is important for educating children regarding self-awareness of disaster preparedness. The sample in this study were children aged 4-5 years, totaling 18 children. The data collection carried out in this study was by observing the pretest and posttest. The data analysis technique in this study used a t-test using the SPSS version 23 program. This research was an experimental study using a one group pretest-posttest design. Based on the results of the pretest and posttest comparisons, comparisons before and after the game house mitigation treatment, it can be seen that most children aged 4-5 years who have been given the treatment have experienced an increase. Based on the normalized gain there is a significant effect. When researchers used mitigation house games to increase self-awareness of disaster preparedness in children aged 4-5 years at PAUD KB Genius Kids, Bukittinggi City, it was 66.43%. Referring to the results of using the G formula, it can be seen an increase in the category of 66.43% in the Moderate category.Keywords: Mitigation House, Self Awareness